Refrigerated storage of the fruits of buriti (Mauritia flexuosa L.) - Fujita, E. [UNESP] (2014)
The objective of this study was to evaluate different storage conditions to maximize the shelf-life of buriti fruits; under ambient conditions the fruits last only 2-3 days. Buriti fruits were stored refrigerated at 10, 12 and 15oC with 85±5% relative humidity, and at room temperature (23±5°C) and 60±5% relative humidity. Fruits were analyzed every three days over a 12-day period for weight loss, respiratory activity, soluble solids, pH, titratable acidity, lipids, protein and fiber. Under the considered conditions, refrigeration at 15oC was found to give the best results.